CMOS Automatic Gain Control Circuit with DC Offset Cancellation for FM/cw Ladar - 赵毅强 徐敏 庞瑞龙 于海霞 赵宏亮 (Transactions of Tianjin University, 2014)
This paper presented an automatic gain control （AGC） circuit suitable for FM/cw ladar. The proposed architecture was based on two-stage variable gain amplifier （VGA） chain with a novel DC offset canceller circuit, which contained an improved Gilbert cell and a Gm-C feedback loop. To keep the VGA with a linearity in dB characteristic, an improved exponential gain control circuit was introduced. The AGC was implemented in 0.18 gm standard CMOS process. Simulation and measurement results verified that its gain ranged from -20 dB to 30 dB, and band- width ranged from 100 kHz to 10 MHz. Its power consumption was 19.8 mW under a voltage supply of 3.3 V.